2013
DOI: 10.1002/cb.1430
|View full text |Cite
|
Sign up to set email alerts
|

‘Shockvertising’: An exploratory investigation into attitudinal variations and emotional reactions to shock advertising

Abstract: This study compares the reactions towards shock advertising in for‐profit (FP) and not‐for‐profit (NFP) organizations. Although the use of shocking advertisements is a growing phenomenon, the findings regarding the effectiveness of such advertisements remain mixed. Moreover, there is little consideration of the use of these tactics in different organizational contexts and the effect on the consumer. A qualitative methodology was adopted and included the use of focus groups to explore the attitudes and emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 53 publications
1
59
0
1
Order By: Relevance
“…We define issue involvement as the extent to which an ad motivates an individual to think about the featured problem (e.g., texting while driving and excessive gambling) and associated consequences. Prior literature suggests that negative content in public service announcements mobilizes and attracts physiological, cognitive, and social resources to a greater extent than does positive content in anti‐piracy messages (Levin et al ., ), as well as anti‐verbal abuse, anti‐smoking, anti‐terrorism and, acquired immune deficiency syndrome prevention messages (Parry et al ., ). The ability of these messages to mobilize individuals' physiological, cognitive, and social resources results in higher levels of issue involvement (Pratto and John, ).…”
Section: Hypotheses and Theoretical Developmentmentioning
confidence: 97%
“…We define issue involvement as the extent to which an ad motivates an individual to think about the featured problem (e.g., texting while driving and excessive gambling) and associated consequences. Prior literature suggests that negative content in public service announcements mobilizes and attracts physiological, cognitive, and social resources to a greater extent than does positive content in anti‐piracy messages (Levin et al ., ), as well as anti‐verbal abuse, anti‐smoking, anti‐terrorism and, acquired immune deficiency syndrome prevention messages (Parry et al ., ). The ability of these messages to mobilize individuals' physiological, cognitive, and social resources results in higher levels of issue involvement (Pratto and John, ).…”
Section: Hypotheses and Theoretical Developmentmentioning
confidence: 97%
“…Because taboos are cultural, different cultures will respond differently to the same product addressing the same taboo [Cheng, 2009]. Parry et al [2013] also found that reactions differed by religion and gender.…”
Section: Cultural Taboos and Product Acceptancementioning
confidence: 99%
“…All of these terms are used synonymously and are defined by many scholars (Dahl et al 2003;Javed, Zeb 2011;Pflaumbaum 2011;Fill 2011;Parry et al 2013;Virvilaite, Matuleviciene 2013) as advertising that is designed to invoke fear, offend and question cultural and social norms.…”
Section: Shocking Advertising Concept Aims and Objectivesmentioning
confidence: 99%